The Relevance Of Marriage Regulation In The Indonesian Civil Code To The Development Of National Marriage Law - Dermina Dalimunthe; Nasruddin Khalil Harahap; Nur Azizah; Sawaluddin Siregar (Sahaja: Journal Sharia and Humanities, 2026)
This study systematically examines the level of relevance of marriage regulations in the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata) to the development of national marriage law and its implications for legal harmonization and legal certainty. The analysis focuses on the paradigm shift in legal regulation following the enactment of Law Number 1 of 1974 on Marriage and the position of the Civil Code within the Indonesian positive legal system. This research is a normative legal study employing statutory, conceptual, and historical approaches. The analysis is conducted through a systematic review of the hierarchy of laws and regulations, the principle of lex specialis derogat legi generali, and the principle of normative harmonization within the national legal system. This study also applies a normative juridical approach by examining statutory regulations, legal doctrines, and relevant court decisions. The findings indicate a paradigm shift from a secular-contractual model toward a religious-administrative model. The Civil Code no longer serves as the primary legal framework governing marriage but instead functions in a residual and complementary capacity, insofar as it does not conflict with the Marriage Law. Normative harmonization through systematic interpretation is therefore essential to ensure consistency and legal certainty in judicial practice.